"Very Early" Intrahepatic Cholangiocarcinoma in Cirrhotic Patients: Should Liver Transplantation Be Reconsidered in These Patients?. Issue 3 (10th January 2014) - Sapisochin, G.; Rodríguez de Lope, C.; Gastaca, M.; Ortiz de Urbina, J.; Suarez, M. A.; Santoyo, J.; Castroagudín, J. F.; Varo, E.; López‐Andujar, R.; Palacios, F.; Sanchez Antolín, G.; Perez, B.; et al.
<x xml:space="preserve">Abstract</x> A retrospective cohort multicenter study was conducted to analyze the risk factors for tumor recurrence after liver transplantation (LT) in cirrhotic patients found to have an intrahepatic cholangiocarcinoma (iCCA) on pathology examination. We also aimed to ascertain whether there existed a subgroup of patients with single tumors ≤2 cm ("very early") in which results after LT can be acceptable. Twenty‐nine patients comprised the study group, eight of whom had a "very early" iCCA (four of them incidentals). The risk of tumor recurrence was significantly associated with larger tumor size as well as larger tumor volume, microscopic vascular invasion and poor degree of differentiation. None of the patients in the "very early" iCCA subgroup presented tumor recurrence compared to 36.4% of those with single tumors >2 cm or multinodular tumors, p = 0.02. The 1‐, 3‐ and 5‐year actuarial survival of those in the "very early" iCCA subgroup was 100%, 73% and 73%, respectively. The present is the first multicenter attempt to ascertain the risk factors for tumor recurrence in cirrhotic patients found to have an iCCA on pathology examination. Cirrhotic patients with iCCA ≤2 cm achieved excellent 5‐year survival, and validation of these findings by other groups may change the current exclusion of such patients from transplant programs.